Viral determinants that drive Enterovirus-A71 fitness and virulence - Pei Yi Ang; Connie Wan Hui Chong; Sylvie Alonso (Emerging Microbes and Infections)
Hand, Foot and Mouth Disease (HFMD) is usually a self-limiting, mild childhood disease that is caused mainly by Coxsackie virus A16 (CVA16) and Enterovirus A71 (EV-A71), both members of the Picornaviridae family. However, recurring HFMD outbreaks and epidemics due to EV-A71 infection in the Western Pacific region, and the propensity of EV-A71 strains to cause severe neurological complications have made this neurotropic virus a serious public health concern in afflicted countries. High mutation rate leading to viral quasispecies combined with frequent intra- and inter-typic recombination events amongst co-circulating EV-A71 strains have contributed to the great diversity and fast evolution of EV-A71 genomes, making impossible any accurate prediction of the next epidemic strain. Comparative genome sequence analyses and mutagenesis approaches have led to the identification of a number of viral determinants involved in EV-A71 fitness and virulence. These viral determinants include amino acid residues located in the structural proteins of the virus, affecting attachment to the host cell surface, receptor binding, and uncoating events. Critical residues in non-structural proteins have also been identified, including 2C, 3A, 3C proteases and the RNA-dependent RNA polymerase. Finally, mutations altering key secondary structures in the 5’ untranslated region were also found to influence EV-A71 fitness and virulence. While our current understanding of EV-A71 pathogenesis remains fragmented, these studies may help in the rational design of effective treatments and broadly protective vaccine candidates.